Effects of SiO2 particles in mechanical properties of iron composite - Amir, Adibah; Mamat, Othman (Trans Tech Publications, 2014)
Tronoh’s raw sand was converted into fine silica particles via a series of milling process. Addition of these fine particles into iron composite was found to modify its mechanical properties. The composite was prepared using powder metallurgy technique with varying percentage of silica particles; 5, 10, 15, 20 and 25wt%. The composites were sintered at three different temperatures; 1000° C, 1100° C and 1200° C to find the most suitable sintering temperature. Changes in density and hardness were observed. The results showed that composite consist of 20wt% silica particles and sintered at 1100° C exhibits best improvement.